Diffusion‐weighted imaging of the high‐risk breast: Apparent diffusion coefficient values and their relationship to breast density. Issue 4 (13th September 2013) - O'Flynn, Elizabeth A.M.; Wilson, Robin M.; Allen, Steven D.; Locke, Imogen; Scurr, Erica; deSouza, Nandita M.
Abstract : Purpose: To document the apparent diffusion coefficient (ADC) of fibroglandular breast tissue in women at high‐risk of developing breast cancer and investigate the relationship between ADC and breast density. Materials and Methods: Local research ethics approval was obtained. A total of 33 high‐risk women including 17 BRCA1/2 mutation carriers (mean age, 43 years) and 16 women postmantle irradiation (mean age 40 years) underwent diffusion‐weighted MRI between days 6 and 16 of their menstrual cycle. ADC histograms from a region of interest in fibroglandular tissue and mammographic breast density measurements were obtained. Mean, percentile ADC values (10th, 25th, 50th, 75th, 90th) and skew were compared for the two groups; ADC and mammographic breast density were correlated. Results: Mean ADC values (×10 −6 mm 2 /s) were 2017 ± 197 in postmantle irradiated women and 1827 ± 289 in BRCA1/2 mutation carriers ( P = 0.035) with significant differences at all percentiles ( P < 0.0001) but not skew ( P = 0.44). ADC values showed weak positive correlation with mammographic breast density in BRCA1/2 mutation carriers ( r = 0.51, P = 0.043) but not in postmantle radiotherapy patients ( r = 0.49, P = 0.13). Conclusion: Higher ADC values seen in fibroglandular tissue postmantle irradiation compared with BRCA1/2 mutation carriers has potential to improve tumor detection in these patients. Lack of correlation between ADC and breast density postmantle irradiation may be a result of microstructural changes.J. Magn. Reson. Imaging 2014;39:805–811. ©2013 Wiley Periodicals, Inc .